Oxidative degradation of aniline derived compounds over carbon based materials - Lasota, Maria Jacinta (2010)
The objectives of this work were: the preparation of different forms of carbon materials (AC, ACSA, CX, CXSA and GBCM), assessment of their catalytic efficiency in the CWPO of the azo dye Chromotrope 2R. Initially the materials were characterized by several techniques, afterwards adsorption and reaction runs were done and lastly the samples obtained from the adsorption/reaction runs were tested using the COD to calculate the organic matter in solution. Reactions were carried out with 100 mg/L C2R solution at 50ºC, pH = 3, hydrogen peroxide of 34.6 mM (5 mL) and 0.5 g/L of carbon material. Several samples (5 mL) were removed from the reactor during 2.5 hours to evaluate the evolution of the dye removal by analysis with UV-VIS (spectrophotometer). The adsorption runs were done the same way, but without hydrogen peroxide. The best results were obtained with Activated Carbon, this material was the best adsorbing material and catalyst, removing 64 % of C2R after 150min of reaction and 74 % the adsorption run. As the reaction results weren´t better than the adsorption ones, iron was incorporated in two of the materials. Incorporating iron in the carbon materials increased radically their catalytic behaviour, with 100 % removal being attained after 150 min of reaction. Os objectivos deste trabalho foram: a preparação de diferentes materiais de carbono (AC, ACSA, CX, CXSA e GBCM) e testar a eficiência destes no CWPO do corante Chromotrope 2R. Inicialmente os materiais foram caracterizados através de várias técnicas, seguidamente foram realizados os ensaios de adsorção e reacção, e no fim, determinou-se a Carência Química do Oxigénio (CQO) das amostras resultantes dos ensaios. As reacções foram feitas numa solução de Chromotrope a 100 mg/L, a 50º C, pH = 3, peróxido de hidrogénio a 34.6 mM (5 mL) e com 0.5 g/L de material de carbono. Foram retiradas várias amostras (5 mL) do reactor durante 2.5 horas, para avaliar a evolução da degradação do corante através da análise com UV-VIS (espectrofotómetro). Os ensaios de adsorção foram feitos da mesma forma, mas sem o peróxido de hidrogénio. Os melhores resultados foram obtidos com o carvão activado que foi o melhor adsorvente e catalisador, removendo 64 % do Chromotrope após 150 min de reacção e 74 % no ensaio de adsorção. Como os resultados da reacção não foram melhores que os obtidos da adsorção, foi incorporado ferro em dois dos materiais. A incorporação de ferro nos materiais de carbono aumentou radicalmente o comportamento catalítico destes, obtendo-se uma remoção de 100 % após 150 min de reacção.